Esthetic evaluation of single implant restorations, adjacent single implant restorations, and implant‐supported fixed partial dentures: A 1‐year prospective study. (7th January 2020) - Boon, L.; De Mars, G.; Favril, C.; Duyck, J.; Quirynen, M.; Vandamme, K.
Abstract: Background: Peri‐implant soft tissues esthetics varies and depends on the restoration type such as implant‐supported single crowns, adjacent multiple single crowns, and fixed partial dentures (FPD). Purpose: The aim of this prospective study was to assess the esthetic outcome of the peri‐implant soft tissues of (NobelBiocare™) implant‐supported single crowns, adjacent multiple single crowns, and FPD. A potential association between the esthetic risk profile and the esthetic outcome was assessed. Materials and methods: Between 03/11 and 03/17, 300 NobelActive implants were installed in 153 partially edentulous patients. Prior to the fabrication of the final restoration, the esthetic risk profile (ERP) of the patient was determined. The pink esthetic score (PES) and white esthetic score (WES) were assessed by three investigators at 6 and 12 months post‐insertion of the final restoration. Patients' appreciation was assessed on a visual analogue scale (VAS) at the 1‐year follow‐up. Results: The clinical acceptable limit for PES (≥6) was achieved in 56% to 68% of the single crowns at 6 and 12 months, respectively. Clinically unacceptable PES scores were recorded for 48% of the adjacent multiple single crowns and 63% of the FPDs at both time points. The association of a high ERP with WES and PESWES was noticed for single implant‐supported crowns. For the latter restoration type, a ≤5 mm distance between the crestal bone level and the proximal contact positively influenced the PES and combined PESWES scores. No correlation was found between PES or WES and patient satisfaction. Mesial papilla formation was more pronounced compared to the distal one for the single implant crowns and for implant‐supported FPD. Conclusion: When high esthetic demands are expected, assessment of ERP prior to implant treatment is advised in order to estimate a realistic outcome.